Factors which affect the catalytic activity of iron(III) meso tetrakis(2,6-dichlorophenyl)porphyrin chloride in homogeneous system - Iamamoto, Y.; Assis, M. D.; Ciuffi, K. J.; Sacco, H. C.; Iwamoto, L.; Melo, AJB; Nascimento, O. R.; Prado, C. M. (Elsevier B.V., 1996)
An optimization study of the reaction conditions of Fe(TDCPP)Cl when it is used as catalyst in the hydroxylation of cyclohexane by iodosylbenzene (PhIO) has been carried out, It was found that Fe(TDCPP)Cl follows the classical PhIO mechanism described for Fe(TPP)Cl, which involves the monomeric active species Fe-IV(O)P-+. (I). In the optimized condition ([Fe(TDCPP) = 3.0 X 10(-4) mol l(-1) in 1,2-dichloroethane (DCE); ultrasound stirring at 0 degrees C; PhIO/FeP molar ratio = 100), this FeP led to a yield of cyclohexanol (C-ol) of 96% and a turnover number of 96, Therefore, Fe(TDCPP)Cl may be considered a good biomimetic model and a very stable, resistant and selective catalyst, which yields C-ol as the sole product. DCE showed to be a better solvent than dichloromethane (DCM), 1 DCE:1 MeOH mixture or acetonitrile (ACN). Since the Fe-IV(O)P-+. is capable of abstracting hydrogen atom from DCM, MeOH or ACN, the solvent competes with the substrate. Presence of O-2 lowers the yield of C-ol, as it can further oxidize this alcohol to carboxylic acid in the presence of radicals, Presence of H2O also causes a decrease in the yield, since it converts the active species I into Fe-IV(OH)P, which cannot oxidize cyclohexane. Addition of excess imidazole or OH- to the system results in a decrease in the yield of C-ol, due to the formation of the hexacoordinated complexes Fe(TDCPP)Im(2)(+) (low-spin, beta(2) = 2.5 X 10(8) mol(-2) l(2)) and Fe(TDCPP)(OH)(2)(-) (high-spin, beta(2) = 6.3 X 10(7) mol(-2) l(2)), the formation of both Fe(TDCPP)Im(2)(+) and Fe(TDCPP)(OH)(2)(-) complexes were confirmed by EPR studies. The catalytic activities of Fe(TDCPP)C and Fe(TFPP)Cl were compared, the unusually high yields of C-ol with Fe(TFPP)Cl obtained when ultrasound, DCM and O-2 atmosphere were used, suggest that a parallel mechanism involving the mu-oxo dimer form, O-2 and radicals may also be occurring with this FeP, besides the PhIO mechanism.
Keywords: cyclohexane; iron(III)porphyrin; oxidation; porphyrin; 2,6-dichlorophenylporphyrin; pentafluorophenylporphyrin; homogeneous catalysis